2010
DOI: 10.1111/j.1600-0714.2010.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of oral yeast colonization and infection in patients with hematological malignancies, head neck and solid tumors

Abstract: The highest incidence of oral candidiasis amongst cancer patients was seen in head neck cancers. The majority of infections were caused by C. albicans but almost one third of patients harbored non-C. albicans strains such as C. glabrata which were often more resistant to anti-fungal agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
71
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 37 publications
11
71
6
1
Order By: Relevance
“…This result is higher thanthose obtained by Schelenz et al (2011), who found a prevalence of oral yeast colonization in 56.8% (227/400) of cancerpatients. C. albicans was also the predominant (74%) specie in this research, followed by C. glabrata (11.5%), C. tropicalis (2.6%), C. krusei (2.6%) and C. parapsilosis (1.9%).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…This result is higher thanthose obtained by Schelenz et al (2011), who found a prevalence of oral yeast colonization in 56.8% (227/400) of cancerpatients. C. albicans was also the predominant (74%) specie in this research, followed by C. glabrata (11.5%), C. tropicalis (2.6%), C. krusei (2.6%) and C. parapsilosis (1.9%).…”
Section: Discussioncontrasting
confidence: 54%
“…C. albicans was also the predominant (74%) specie in this research, followed by C. glabrata (11.5%), C. tropicalis (2.6%), C. krusei (2.6%) and C. parapsilosis (1.9%). Finally, this and others authors reported a significant increased risk of clinical oral fungal infection during cancer therapy (Lalla et al, 2010;Schelenz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In France, in one hospital, 17% of neutropenic patients with acute leukemia were colonized with C. kefyr (13), whereas in three other hospitals, 4.8% of all Candida isolates from hematology wards were C. kefyr (more than twice as many as in nonhematology wards) (14). In contrast, C. kefyr accounted for only 0.7% of Candida species found in the oral cavity of cancer patients in a United Kingdom regional center (15), and this species was not found among candidal surveillance cultures in patients with HM treated in a Finnish hospital (16).…”
Section: Andida Kefyr (Formerly Candida Pseudotropicalis) Is a Yeasmentioning
confidence: 94%
“…Schelenz et al [2] isolated 266 oral yeasts of the Candida genus from patients with hematological malignancies and head and neck solid tumors and found that 28.2% of the isolates were resistant and 23.7% were susceptible dose dependant (SDD) to fluconazole, itraconazole, ketoconazole, voriconazole, and caspofungin. The majority of these resistant strains were C. glabrata and C. krusei.…”
Section: Introductionmentioning
confidence: 99%
“…However, other non-Candida albicans emerging species have arisen, such as C. dubliniensis, C. lusitaniae, C. rugosa, C. norvegensis, C. kefy, C. lypolitica, and C. guilliermondii, due to a growing population of immunosuppressed patients and the use of broad-spectrum antibiotics [1,2]. Yeasts from the Candida genus are responsible for the majority of fungal infections in immunocompromised patients owing to the use of immunosuppressive drugs and characteristics of the individual, such as advanced age and systemic diseases.…”
Section: Introductionmentioning
confidence: 99%